Physical properties and corrosion behaviour of Co-Cr-Ni alloy developed by powder metallurgy - Raudhah Othman (School of Materials Engineering, 2011)
In this study, a composition of cobalt-chromium (Co-Cr) and ten series of cobalt-chromium-nickel (Co-Cr-Ni) alloys were fabricated using powder metallurgy technique. The objectives of the research are: to develop Co-Cr-Ni alloys by powder metallurgy; to correlate physical and mechanical properties such as density, porosity, shrinkage and hardness with composition of Co-Cr-Ni alloys and to understand a relationship of corrosion resistance with composition of Co-Cr-Ni alloy by immersion test.